PENERAPAN AUGMENTED REALITY PADA APLIKASI PENGENALAN HEWAN KEPADA ANAK ANAK MENGGUNAKAN USER CENTERED DESIGN - halim, jeffrey; Edy, Edy (Fakultas Sains dan Teknologi-Universitas Buddhi Dharma, 2023)
Currently we are in the era of globalization, this means that information is becoming easier to obtain and also easier to access. One tool developed to take advantage of this era is a smartphone. with smartphones we can access information from anywhere and anytime. Augmented reality aims to unite reality and the virtual world by bringing virtual goods into the real world through our smartphone layer. This is very good because augmented reality is very useful in many ways. Even though it is useful in many ways, augmented reality is still rarely used because this technology is practically a new technology that is still being developed, because this technology is still relatively new, most people see this technology and ignore it or don't even know about this technology. Therefore this study aims to bring awareness to this technology by creating an animal recognition application using augmented reality. This research is a research on designing animal recognition learning applications for children using the user centered design method. In this study, a survey method was used from 6 respondents from around me.